Kütüphan-e Türkiye Project with WH Questions - Ahmet Çelik (Türk Kütüphaneciliği)
Today Internet is the most important tool for accessing information. But such a large segment of the society can not utilise this opportunity thus we meet with the fact which is called “digital divide”. The public libraries are accepted as the most suitable alternative to deal with this problem. Bill and Melinda Gates Foundation provides financial support to the public libraries of developing countries, through Global Libraries Initiative. In Turkey, for this purpose, General Directorate of Public Libraries and Hacettepe Technopolis - Technology Transfer Center have initiated a R&D Project called Librar-e Turkey Planning and Piloting. In this essay, the Project is described from different aspects.